Innervated Biomaterials for Improved Cutaneous Wound Healing: A Review of Recent Advancements and Future Prospects - Zhang B; Zhang K; Liu Q; Zhang J; Chen W; Tang J; Wang C; Guo Z (International Journal of Nanomedicine)
BoYang Zhang,1,* KaiYue Zhang,1,* QiuYue Liu,1 JiaLin Zhang,1 WenTao Chen,1 JieTing Tang,1 Chuang Wang,2 ZhenZhao Guo1 1School and Hospital of Stomatology, Guangdong Engineering Research Center of Oral Restoration and Reconstruction, Guangzhou Medical University, Guangzhou, 510180, People’s Republic of China; 2Foshan Stomatology Hospital, School of Medicine, Foshan University, Foshan, 528099, People’s Republic of China*These authors contributed equally to this workCorrespondence: ZhenZhao Guo, School and Hospital of Stomatology, Guangdong Engineering Research Center of Oral Restoration and Reconstruction, Guangzhou Medical University, Guangzhou, 510180, People’s Republic of China, Email Guozhenzhao2008@126.comAbstract: Cutaneous wound healing remains a significant clinical challenge, particularly for chronic and large-scale injuries, where functional recovery—especially sensory reinnervation—is often inadequate. Recent advances highlight the pivotal role of innervation in regulating tissue repair through neuropeptide signaling, immunomodulation, and angiogenesis. Despite progress in biomaterial-based therapies, most existing solutions focus on structural repair while neglecting neural regeneration, leading to suboptimal functional outcomes. This review explores emerging biomaterial strategies that integrate neuroregenerative capabilities with wound healing properties, including electroconductive scaffolds for bioelectric stimulation, neurotrophic factor-releasing matrices, and bioengineered constructs. We critically evaluate their mechanisms in promoting axonal regrowth, macrophage polarization, and vascular network formation, while addressing challenges in long-term functional integration. This review outlines the mechanisms of wound healing, existing treatments, and the vital role of nerves in the healing process. It also highlights materials that promote skin neuralization in cutaneous wound healing, aiming to inspire further research into these materials and the underlying mechanisms involved. By bridging the gap between neural and cutaneous regeneration, this work provides a roadmap for developing next-generation wound therapies that restore both structural integrity and sensory function. Future directions emphasize the need for standardized neuroregenerative assessment criteria and clinically translatable designs. Keywords: cutaneous wound, innervation, neuro regenerative materials